OPTIMALISASI KINERJA SUMBER DAYA MANUSIA DALAM MENINGKATKAN KUALITAS PELAYANAN PASPOR DI KANTOR IMIGRASI KELAS II TPI SIBOLGA - Rivaldo A nugerah Zendrato; Rahmawati Nurul Jannah; Rasona S Sunara Akbar (Polteknik Imigrasi, 2022)
The geographical condition of the work area and 2 Office Work Units is not balanced with the number of human resources available at the Sibolga Immigration Office, so that the immigration services provided are not optimal. The realization of maximum immigration services is influenced by several aspects, one of which is employee performance. The purpose of this study was to find out how to optimize the performance of human resources in improving the quality of passport services at The Immigration Office (Class II) of Border Controls Sibolga and to find out what factors were inhibiting and supporting the performance of human resources in improving the quality of passport services at The Immigration Office (Class II) of Border Controls Sibolga. This study used qualitative research methods. The data was obtained by conducting interviews with employees and applicants at the Immigration Office Class II TPI Sibolga. Then observations were made to observe and know firsthand the optimization of the performance of human resources at the Sibolga Immigration Office. Furthermore, an analysis of the data that has been obtained is carried out. From the results of this study, it is known that the optimization of the performance of human resources in improving the quality of passport services at The Immigration Office (Class II) of Border Controls Sibolga is carried out by providing motivation to employees, giving rewards and punishments (reward and punishment), training human resources and improving facilities and infrastructure. Office. The supporting factors for employee performance at the Sibolga Immigration Office include support from the local government and employee work discipline, the implementation of work discipline at The Immigration Office (Class II) of Border Controls Sibolga is divided into two, namely preventive work discipline and corrective work discipline. Then the inhibiting factor for employee performance at the Sibolga immigration office is the lack of human resources and the utilization of facilities and infrastructure is not optimal.